Pedestrian Facility Analysis For Utilization and Comfort - Widodo Budi Dermawan; Nuzul Ardi Daputro (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
As the population continues to grow, it results in a lot of human mobility. However, the high mobility is not matched by transportation facilities and infrastructure services, especially the sidewalks. One of the areas with existing sidewalk problems is Bekasi Highway KM. 18. The problems that occur are that the sidewalks are used as a place to sell street vendors, are used as illegal parking lots and the unavailability of guide tiles for persons with disabilities. The methodology of this research is carried out by conducting geometric surveys, measuring the volume and travel time of pedestrians to determine service levels and distribute questionnaires to 63 respondents to pedestrians in finding the level of performance and the importance of sidewalk facilities. The processing of this data uses Microsoft Excel and the Statistical Package for the Social Sciences (SPSS) using the Importance Performance Analysis (IPA) method. The results of the analysis carried out by geometric surveys show that the sidewalks have not met the minimum standards according to regulations. From the measurement results of the volume and travel time of pedestrians, the service level is obtained with category B, as well as the results of the questionnaire related to the level of performance and the importance of sidewalk facilities, namely quadrant I there is Circulation, Climate, Shape, Safety, Cleanliness, Beauty, in quadrant II there is Circulation, Noise, Smells, Cleanliness and in quadrant III there is Circulation, Noise, and Cleanliness.